Analisis Perbuatan Melawan Hukum dalam Perjanjian Konsesi Pelabuhan (Studi Kasus: Putusan Pengadilan Negeri Jakarta Utara Nomor 70/Pdt.G/2018/Pn.Jkt Utr) - Samosir, Jeffry P (Jurnal Suara Hukum, 2020)
Acts against the law have a wider scope than criminal acts. Provisions regarding acts against the law are regulated in Article 1365 of the Civil Code which states "every act against the law that brings harm to others, obliges the person because of the mistake of issuing the loss, compensating the loss". In the North Jakarta District Court Decision Number 70/Pdt.G/2018/Pn.Jkt Utr) "The judge stated that PT. Karya Citra Nusantara and the Ministry of Transportation have committed acts against the law to PT. Kawasan Berikat Nusantara by entering into a concession agreement Number HK.107/1/9 KSOP.Mrd-16 Number 001 / KCN KSOP/ Concession/XI/2016 concerning Exploitation of Port Services at the PT Karya Citra Nusantara Public Terminal in Marunda Port. There are three problem formulations in this study including; (1) What is the legal provisions for the port concession agreement in Indonesia? (2) Is the North Jakarta District Court Decision in accordance with the provisions of the law in force in Indonesia? (3) What is the legal effect of the investment made by investors against PT. Karya Citra Nusantara based on the North Jakarta District Court Decision? Based on the three formulation of the problem, the writer conducts an analysis of unlawful acts in the concession agreement based on the decision of the North Jakarta District Court Number 70/Pdt.G/2018/Pn.Jkt Utr". This study uses a type of legal/juridical research approach